Manajemen laba bank syariah berdasarkan independensi dan efektivitas komite audit - Putri, Disna Hilda Rosita; Maesaroh, Dewi (Islamic Accounting Journal, 2023)
This study aims to test the relationship between independence, expertise, frequency of meetings and audit committee time commitment to profit management. This research uses quantitative approach which uses 14 Sharia Commercial Bank Companies in Indonesia with Purposive Sampling data retrieval techniques and the remaining 9 companies. The data was analyzed using Multiple Regression Analysis. The results of this study show that partial independence, expertise, frequency of meetings and commitment of audit committee time have a significant effect on profit management. While simultaneously the independence, expertise, frequency of meetings and commitment of audit committee time have no significant influence on profit management.